'DATA BARU' DARI DISTRIBUSI ARTEFAK PRASASTI - Kusumohartono, Bugie (Berkala Arkeologi, 1994)
The purpose of archaeological studies here is to cover what Spaulding (1971) mentioned with the dimensions of each artifact. According to him, artifacts have three dimensions, namely form (formal), space (spatial), and time (temporal). Archaeological analysis is based on the interrelation between the three dimensions, for example the dimensions of form and time, dimensions of time and space, or dimensions of form and space.